Preexposure Prophylaxis and Patient Centeredness: A Call for Holistically Protecting and Promoting the Health of Gay Men. (September 2016) - Snowden, Jonathan M.; Rodriguez, Maria I.; Jackson, Skyler D.; Marcus, Julia L.
Preexposure prophylaxis has transformed HIV prevention, becoming widespread in communities of gay and bisexual men in the developed world in a short time. There is a broad concern that preexposure prophylaxis will discourage condom use among gay men (i.e., "risk compensation"). This commentary argues for broadening the focus on gay men's health beyond sexual health to address the holistic health and well-being of gay men. Gay men may benefit from being offered candid, nonjudgmental health promotion/HIV prevention messages not requiring condom use for anal sex. Lessons can be drawn from the family planning movement, which has undergone a similar shift in focus. The principle of patient centeredness supports such a shift in gay men's health toward the goal of providing men with the knowledge to evaluate various prevention approaches according to the specifics of their life circumstances and health needs. Bringing more nuance to discussions of sexual risk and sexual pleasure could facilitate more universally healthy attitudes regarding sex among gay men, in turn enabling healthier decisions more compatible with men's own values and preferences.